Notice of Four Ancient Scottish Standards, with Detailed Description of the Recently Discovered Marchmont Standard (Proceedings of the Society of Antiquaries of Scotland, 1918)
The Standard, which was very long and narrow in proportion to its length and terminated in a pointed, rounded, or swallow-tailed end was originally designed for fixing immediately below the head of a lance, and then styled a Pennon, gradually evolved a much more ornate character. The flag was no longer an appendage to a\r lance but was carried on a pole shaft of its own, and served as a rallying point or as indicating the noble or knight to whom his attendant "plump of spears" and other vassals belonged. The Cavers Standard, the Standard of Keith, Earl Marischal, the Bellenden Standard and the Marchmont Standard are described in detail.